2011
DOI: 10.1167/iovs.11-8388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Sex, and Axial Length on the Three-Dimensional Profile of Normal Macular Layer Structures

Abstract: Macular layer thicknesses measured on SD-OCT images in healthy eyes showed significant variations by sex and age. These findings should inform macular layer thickness analyses in SD-OCT studies of retinal diseases and glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
239
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(292 citation statements)
references
References 50 publications
46
239
4
3
Order By: Relevance
“…Neither the presence of any DR at inclusion, nor progression of DR after inclusion was associated with any change in the NFL or GCL+IPL, nor did age, blood pressure, or HbA1c level influence the thickness of the NFL or GCL-IPL. As expected, female sex was associated with significantly thinner parafoveal NFL and GCL at inclusion (22).…”
Section: Resultssupporting
confidence: 81%
“…Neither the presence of any DR at inclusion, nor progression of DR after inclusion was associated with any change in the NFL or GCL+IPL, nor did age, blood pressure, or HbA1c level influence the thickness of the NFL or GCL-IPL. As expected, female sex was associated with significantly thinner parafoveal NFL and GCL at inclusion (22).…”
Section: Resultssupporting
confidence: 81%
“…An age-matched control group was used to compare retinal layer thickness in the study groups [13,14] . Gender was taken in consideration, as retinal layer thickness measured on Cirrus SD-OCT in healthy eyes showed significant variations by gender [13,15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies using SD-OCT showed similar symmetrical thicknesses of the GCL, IPL, and GCLþIPL of healthy eyes in an elliptical annulus. 7,10,13,19,26 The GCIPL thicknesses on all 360 spokes should be equivalent if the symmetry is perfect; and, consequently, the initial RGC loss limited to a small local area would be detectable as a decrease of the GCIPL thickness on the spokes, leading to minimum GCIPL thickness. Thus, this parameter should theoretically detect early or initial RGC loss with high sensitivity.…”
Section: Discussionmentioning
confidence: 99%